Standardized Neurodevelopmental Surveillance of High-risk Infants Using Telehealth: Implementation Study during COVID-19. Issue 4 (28th July 2021) - Maitre, Nathalie L.; Benninger, Kristen L.; Neel, Mary Lauren; Haase, Jennifer A.; Pietruszewski, Lindsay; Levengood, Katelyn; Adderley, Kathleen; Batterson, Nancy; Hague, Kaleigh; Lightfoot, Megan; Weiss, Sarah; Lewandowski, Dennis J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Neurodevelopmental surveillance is critical for high-risk infants following neonatal intensive care discharge and is traditionally performed in-person. COVID-19 interruption of regular surveillance necessitated a rapid development of telehealth models for effective and standardized care. Methods: We used implementation science and lean methodologies to develop an effective telehealth neurodevelopmental surveillance program for high-risk infants. Interventions included reorganization of visit flow processes and a telehealth toolkit for standardized neurological and developmental assessments. We tested and improved our intervention through plan-do-study-act cycles, value-added analysis, and parent- and provider-satisfaction questionnaires. Process metrics (standard elements, subspecialty referrals, diagnostic tests, and prescriptions ordered) were compared in group-level analyses between telehealth patients (N = 97) March 16, 2020–July 1, 2020 and a matched in-person cohort at the same period the previous year. Run charts examined shifts in balancing measures (provider efficiency and missed visits) over 8 weeks before and after implementation. Results: Primary outcomes were visit completion (100%), patient parent satisfaction (>90% strongly agreed or agreed telehealth procedures were valuable and easy to use) and ability to accurately diagnose cerebral palsy (no statistical difference with comparison visits). Providers (N = 6) rated telehealth experiences favorably. Process metrics indicated no differences between telehealth and in-person visits (all P > 0 .05). Following telehealth implementation, provider efficiency increased to near baseline (median 88.9% versus 91.7%) and median missed visits decreased to 0% from 20% (in-person). Conclusions: Implementation of telehealth for neurodevelopmental surveillance in a tertiary high-risk infant follow-up clinic successfully provided standardized and timely care during stay-at-home orders; broader telehealth applications may overcome access barriers in this field.